Transition of Care from Pediatric to Adult Care in Eosinophilic Esophagitis: Insights From a Patient Perspective Survey. Issue 6 (17th December 2021) - Robinson, Jane; Furuta, Glenn T.; Hadker, Nandini; Kolev, Irana; Williams, James; Juethner, Salomé; Falk, Gary W.
Abstract : Supplemental Digital Content is available in the text Abstract : ABSTRACT: Eosinophilic esophagitis (EoE) is a chronic immune-mediated disease. Patients with a childhood diagnosis require ongoing disease management in adulthood; however, knowledge of the patient experience during pediatric to adult healthcare transition is lacking. Here, an online survey captured patient perceptions of the challenges faced by patients with EoE in the United States during transition to adult healthcare, and which resources, if implemented, could better support transition. Of 67 respondents, 91% (n = 61) were under adult care at the time of survey completion. Aspects that respondents struggled with most included meal planning, food shopping, cooking/finding foods that did not exacerbate their condition, and knowledge of insurance coverage. Although most respondents reported confidence in having the knowledge to manage their EoE, almost half of the respondents worried about managing their condition in the future. Resources detailing diet, medication and insurance management strategies could support the transition to adult healthcare for patients with EoE.